2012
DOI: 10.1620/tjem.227.73
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Worsens the Surgical Outcomes in Cirrhotic Patients with Hepatocellular Carcinoma

Abstract: Diabetes is a known risk factor for developing hepatocellular carcinoma (HCC). Reported rates of diabetes are higher in chronic hepatitis, cirrhosis and HCC patients. However, its effects on postoperative recurrence and survival with HCC are controversial. This study offers a retrospective analysis of the impacts of diabetes on postoperative recurrence and survival in patients with cirrhosis and HCC. A total of 389 cirrhotic patients who underwent curative resection for primary HCC at our institution between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…These findings are also consistent with previous studies which reported that vascular invasion, tumor size (≤ 3 cm or ≤ 5 cm, or > 3 cm) and the number of tumor lesions appears to affect prognosis in DM patients compared with non-DM patients[23,29,31,33]. The current findings suggest that DM may be related to pathological features of tumors that affect long-term survival post-LT in HBV-related HCC patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are also consistent with previous studies which reported that vascular invasion, tumor size (≤ 3 cm or ≤ 5 cm, or > 3 cm) and the number of tumor lesions appears to affect prognosis in DM patients compared with non-DM patients[23,29,31,33]. The current findings suggest that DM may be related to pathological features of tumors that affect long-term survival post-LT in HBV-related HCC patients.…”
Section: Discussionsupporting
confidence: 92%
“…The current study suggests that DM may be related to older age (> 50 years) and poor liver function (ALT or AST levels 40-80 IU/L, Child-Pugh score B), which may affect outcomes post-LT. A previous study of 389 patients with HCC and cirrhosis by Ting et al[31] reported that DM, Child-Pugh scores (B and C) and AST levels were significant risk factors affecting HCC prognosis after surgical resection. Huo et al[32] reported that elderly and DM patients were associated with hepatic decompensation.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies concerning the postoperative outcomes of HCC patients, some focused on associated risk factors and compared survival rates (Ker et al 2003;Chok et al 2009;Ju et al 2009;Ting et al 2012). While some others used log rank test for univariate analysis, followed by Cox proportional hazards regression models for multivariate analysis in consecutive series of patients (Poon et al 2000;Sasaki et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The patients' gender and age, the accompany disease, pathological status of the liver, original tumor, and treatmentrelated factors are related to postoperative survival in HCC patients (Qin and Tang 2002;Chok et al 2009;Ting et al 2012). However, controversy existed for which of these factors are the most important on different stage of the disease after hepatic resection.…”
mentioning
confidence: 99%
“…In addition, systemic inflammation, which can induce insulin resistance through reducing insulin sensitivity, is also involved in various stages of HCC tumorigenesis (1315). Further studies have demonstrated that pre-existing DM can worsen the outcome of patients with HCC undergoing surgical and non-surgical therapy (1618), and that systemic inflammation markers, including the neutrophil to lymphocyte ratio (NLR), can also predict the survival of HCC patients (19). However, little information has been focused on the effect of pre-existing DM and baseline NLR on the overall survival (OS) rate of non-viral HCC.…”
Section: Introductionmentioning
confidence: 99%